Pemberdayaan Masyarakat melalui Program Tempat Sampah dan Apotek Hidup sebagai Upaya Mewujudkan Lingkungan Bersih dan Sehat di RT 3 RW 1 Kelurahan Sawah Lebar - Yessi Indah Radianti; Zahza Ivana Putri; Jelita Puja Afrianti; Novia Azelia; Yenni Fitria; Suwarni Suwarni; Karona Cahya Susena (Jurnal Kewirausahaan dan Bisnis, 2026)
This community service activity was carried out through the Kuliah Kerja Nyata (KKN) program in RT 3 RW 1, Sawah Lebar Village, Bengkulu City. The program aimed to improve environmental cleanliness and community health through the provision of trash bins and the development of a family medicinal plant garden (apotek hidup). The problems faced by the community included limited waste disposal facilities and the underutilization of home yards for productive purposes. The implementation method used a participatory approach consisting of observation, program planning, socialization, implementation, assistance, and evaluation. The results showed increased community awareness and participation in maintaining environmental cleanliness and utilizing home yards productively. Overall, the program contributed positively to creating a clean and healthy environment through community empowerment.